Enhancing Character Education Through Monopoly Game-Based Discovery Learning in Indonesian Secondary Schools (JED (Jurnal Etika Demokrasi), 2025)
The growing concern over the decline of character values among students underscores the urgent need for effective educational interventions in Indonesian secondary schools. This study aims to evaluate the effectiveness of a Monopoly game-based discovery learning model in strengthening character education among eighth-grade students. Employing a quasi-experimental, mixed-methods design, the research involved selected student cohorts and teachers at SMP Negeri 18 Kota Malang, utilizing validated questionnaires, observation checklists, interviews, and statistical analysis including Spearman’s correlation. The findings reveal that the integration of Monopoly game media within discovery learning significantly enhances students’ engagement, critical thinking, and internalization of key character values such as honesty, empathy, self-control, and cooperation. The empirical evidence demonstrates marked improvements across all measured aspects of character education, confirming the model’s impact in both affective and behavioral domains. The study concludes that the Monopoly game-based discovery learning model effectively fosters character development in classroom settings. The novelty of this research lies in its systematic combination of game-based and discovery-oriented pedagogies tailored for character education, filling a gap in existing educational practice. This study contributes substantially to the advancement of pedagogical strategies for moral and civic education, offering a replicable model for fostering holistic student development in diverse learning environments.
Keywords: Character Education; Discovery Learning; Monopoly Game; Secondary School; Indonesia